Pengaruh GCG Terhadap Profitabilitas dari Aspek EPS Pada Perusahaan Basic Industry dan Chemical - Y, Amril; Nasfi (El-kahfi | Jurnal Ekonomi Islam, 2022)
This study aims to analyze the effect of Institutional Ownership (INST), Number of Directors (DIR), Independent Commissioners (INDEP) and Audit Committee (AUD) as a structural part of Good Corporate Governance (GCG) on company profitability as a proxy for Earnings Per Share (EPS). in Basic and Chemical Industry companies listed on the Indonesia Stock Exchange (IDX). This type of research is descriptive, a population of 64 companies, a sample of 25 companies in 2014-2017 listed on the IDX, with multiple linear regression analysis testing using Eviews in processing the data. The results of the analysis of each independent variable with the dependent variable show that: (1) Institutional Ownership (INST) has a coefficient value of -0.471696 and a p-value of t-stat 0.2990 which means negative and not significant, (2) the coefficient of Directors (DIR) value -0.043827 and p-value t-stat 0.9044 which means negative and insignificant effect, (3) Independent Commissioner (INDEP) has a coefficient of 0.654381 and p-value t-stat 0.0000 means positive and significant effect, (4) Audit Committee (AUD) has a coefficient value of -1.038939 and a p-value of t-stat 0.0000 which means a negative but significant effect. Meanwhile, simultaneously obtained the R2 value of 0.025736, which means that the independent variable cannot explain the Earning Per Share (EPS) variable as the dependent variable with an effect of only 2.57%. So that as much as 97.43% is influenced by other variables that are not discussed in this study. Finally, the researcher concludes that Institutional Ownership, Number of Directors, Independent Commissioners and Number of Audit Committees cannot affect the company's profitability in absolute terms from the aspect of Earning Per Share (EPS). The magnitude of the influence on the profitability of a company can come from the system and process of implementing GCG or from other factors that require further research.